(untitled) (Stato, Chiese e pluralismo confessionale, 2015)
Contributo sottoposto a valutazione. SOMMARIO: 1. Preambolo – 2. Valore teologico e valore giuridico dei pronunciati del Magistero ecclesiastico – 3. La lectio magistralis del 12 maggio 2003 di Giovanni Paolo II – 4. La Carta di Sant’Agata de’ Goti del 29 settembre 1997 e la legge italiana 25 luglio 2000 n. 209 – 5. La sfida dei Pontificati di Benedetto XVI e di Francesco – 6. Autorità politica mondiale e giustizia sociale – 7. L’umanesimo cristiano oggi – 8. Sintesi conclusiva. Abstract Catholic Ethics, Debt and Social Justice in the Light of a New International Order Since twenty years a group of scholars, including the Author of this essay, has been fighting for the reconstruction of the legal framework of the international debt. The Charter of Sant’Agata de’Goti (September 29, 1997), which is the result of the passionate work by a Commission on usury and international debt, has virtually been travelling around the world, including the Latin American Parliament and the Vatican City, finally landed in the Italian Parliament with the 25 July 2009 Italian Act (n. 209). Besides the legal relevance, this essay is the testimony of a significant part of the service that the Author has carried out in the interest of the Holy See and the Catholic Church; this is in fact a summary of his twenty-year commitment on the (public-private-international) debt, in view of the forthcoming visit of the Holy Father Francis in the United States (September 2015), on the eve of the 2015-2016 Extraordinary Jubilee Year (called the “Holy Year of Mercy”), which again will underline the principle of natural order for all the goods on earth. This papal journey assumes considerable importance, especially when related to the Pope’s speech, which will be held at the Congress and at the General Assembly of the United Nations in New York. The Author of this essay hopes that, in the context of those venerable international institutions, together with the Italian government, the Holy Father – under his personal commitment which is recognized in the world – will propose to the UN Assembly the start of the procedures for requesting the opinion of the AIA Court of Justice about the consistency between the rules governing the developing Countries’ foreign debt (but today you might be referring to the international debt tout court) and the framework of human rights principles, which includes the rights of peoples. We must also keep in mind that, in order to better understand the frame of reference, a deputy of the Italian Chamber, Salvatore Cherchi, together with other proponents of the mentioned 2000 Act (n. 209) – whose Article 7 remained unfulfilled – have been directly inspired by the mentioned Charter of Sant’Agata de’Goti on usury and international debt.